2015
DOI: 10.1088/0004-637x/812/1/42
|View full text |Cite
|
Sign up to set email alerts
|

Starspot Distributions on Fully Convective M Dwarfs: Implications for Radial Velocity Planet Searches

Abstract: Since M4.5 -M9 dwarfs exhibit equatorial rotation velocities of order 10 kms −1 on average, radial velocity surveys targeting this stellar population will likely need to find methods to effectively remove starspot jitter. We present the first high resolution Doppler images of the M4.5 dwarf, GJ 791.2A, and the M9 dwarf, LP 944-20. The time series spectra of both objects reveal numerous line profile distortions over the rotation period of each star which we interpret as starspots. The transient distortions are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 54 publications
7
74
0
Order By: Relevance
“…Although relying on a simple assumption, this method gives promising results, and allows us to get a better insight on the origin of the activity RV jitter of early M dwarfs. This study of slowly-rotating early-M dwarfs complements the analysis already done for late M dwarfs (e.g., Barnes et al 2011Barnes et al , 2014Barnes et al , 2015.…”
Section: Photosphere Occupancysupporting
confidence: 68%
“…Although relying on a simple assumption, this method gives promising results, and allows us to get a better insight on the origin of the activity RV jitter of early M dwarfs. This study of slowly-rotating early-M dwarfs complements the analysis already done for late M dwarfs (e.g., Barnes et al 2011Barnes et al , 2014Barnes et al , 2015.…”
Section: Photosphere Occupancysupporting
confidence: 68%
“…Mid-to late-M dwarfs have also been found to have abundant polar spots from Doppler imaging. Barnes et al (2015) found the M4.5 dwarf GJ791.2A to have a mean spot coverage of 3.2% and a maximum spot coverage of 82.3% during its rotation, assuming spots are 300K cooler than the photosphere. On the Sun, spots are accompanied by bright plage, which include faculae with temperature contrasts of 300-500K with their surroundings (Topka et al 1997).…”
Section: Physical Interpretation Of Cpat Modelmentioning
confidence: 99%
“…The spectra S o and S u are generated using the values for Fe H o [ ] and Fe H u [ ] (the metallicities of the occulted and unocculted spectra, respectively) and linearly interpolating between the closest spectra in the PHOENIX model grid. Following the results of Doppler imaging studies of Mdwarfs, we adopt = F 0.032, which is the mean spot filling factor Barnes et al (2015) found for the M4.5dwarf GJ791.2A over its rotation period. We fix the metallicity of the occulted spectrum to the best-fit value for the metallicity of GJ1214, ) using the mean and standard deviation of the residuals found by fitting the joint data set to the exoplanetʼs model transmission Figure 6.…”
Section: Cpat Model For Absorber Heterogeneitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a scenario has been suggested to explain observations of the late-type EB H II 2407 in the Pleiades . Indeed, there is observational evidence (Barnes et al 2015) and theoretical motivation (Schuessler & Solanki 1992;Granzer et al 2000) for polar spots on rapidly rotating, fully convective stars.…”
Section: Spin−orbit Synchronizationmentioning
confidence: 99%